Factors driving growers' selection and implementation of an apple crop protection strategy at the farm level. (October 2016) - Pissonnier, Solène; Lavigne, Claire; Toubon, Jean-François; Le Gal, Pierre-Yves
Abstract: While protecting their crops, apple growers must also satisfy the requirements of their buyers regarding pesticide residues and fruit characteristics. Based on an analysis of farm pesticide application schedules and semi-structured interviews of 35 apple growers in two areas of France, this study described how growers designed and implemented their apple protection strategies, and identified the factors which helped and/or prevented them from using less pesticide. Different combinations of economic and environmental concerns led to three main protection strategies. Growers implementing the bio-ecological strategy (S1) had high environmental concerns, used no synthetic pesticides, and compensated their lower yields with high selling prices. Growers implementing the combined strategy (S2) had moderate environmental concerns. They planted scab-resistant varieties and sprayed natural products, while diversifying their outlets and cultivars to compensate for low selling prices. The low risk strategy (S3) was implemented by growers from cooperatives with low environmental concerns who aimed for high yields and visual quality by using mainly synthetic pesticides. S2 and S3 growers were constrained by low selling prices and by the increased workload and economic risks represented by alternative methods. Extending the range of alternatives to pesticides and implementing innovative advice methodologies could be levers to reduce pesticide use. Highlights: Protection practices of apple growers show a high diversity in a common context. Economic and environmental concerns lead to three types of protection strategies. Each type corresponds to specific farm circumstances. Low apple prices, high workload and economic risks prevent decreasing pesticide use. Decreasing pesticide use requires for innovative advice at farm level.